Law Enforcement on Electronic Waste Pollution in Sidoarjo: Penegakan Hukum terhadap Pencemaran Limbah Elektronik di Sidoarjo - Rahmawati, Yuli; Rosnawati, Emy (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Environmental pollution from electronic waste has become a significant issue in Indonesia, especially in Sidoarjo, where improper disposal causes serious health and ecological risks. Specific Background: Despite existing environmental regulations, their enforcement at the regional level remains limited and inconsistent. Knowledge Gap: Previous studies focused more on waste management systems rather than on legal enforcement processes and administrative accountability. Aims: This study aims to analyze the implementation of environmental criminal law against electronic waste polluters in Sidoarjo Regency. Results: The findings show that law enforcement conducted by the Sidoarjo Environmental and Hygiene Service has not been optimal due to limited authority, inadequate facilities, and public indifference. Novelty: This study highlights the gap between legal norms and actual practices in local law enforcement. Implications: Strengthening interagency coordination and public awareness is essential to achieve effective electronic waste regulation and sustainable environmental governance. Highlights: Electronic waste law enforcement in Sidoarjo Legal and administrative challenges Community awareness in environmental protection Keywords:Electronic Waste, Law Enforcement, Environmental Regulation, Local Government, Sidoarjo